Soil nitrogen fertilisation as a maternal effect on Buglossoides arvensis seed germinability. (25th September 2016) - Longas, M M; Chantre, G R; Sabbatini, M R
Summary: Different ecological strategies are developed by weed species to improve their fitness under unpredictable environmental conditions. Maternal effects are a way to enhance the performance of progeny. The external ecological environment of mother plants influences phenotypic traits of the progeny, such as seed germinability. Buglossoides arvensis is a facultative winter annual weed species present in cereal crops of the semiarid temperate region of Argentina. Recently, the intensification of agricultural systems has led to a significant increment of external inputs, such as nitrogen fertilisers. In this work, we aimed to determine the effect of different maternal nitrogen fertiliser levels on the germinability of two successive progenies (F1 –F2 ). A population‐based model was used to estimate thermal time parameters. Our results indicated that under field conditions, nitrogen fertilisation produced an increment on the germinability of the progeny. Nitrogen supply promoted a widening of the permissive germination thermal range through an increment in the mean maximum germination temperature. However, different maternal fertilisation levels did not influence germination thermal time requirements either in F1 or F2 progenies. It might be inferred that a significant increment of nitrogen fertiliser supply could increase the probability of occurrence of very early emergence fluxes of B. arvensis . From a weed control perspective, the occurrence of early cohorts during summer may demand a redesign of control tactics, to minimise the potential economic and environmental impact of chemical interventions.